Graft and patient survival after renal transplantation in the period from 1996 to 2017 at the Military Medical Academy, Belgrade, Serbia - Vavić, Neven; Tomić, Aleksandra; Aleksić, Predrag; Obrenčević, Katarina; Radojević, Milorad; Ignjatović, Ljiljana; Marić, Predrag; Jovanović, Mirko; Rančić, Nemanja; Maksić, Djoko (Vojnosanitetski pregled, 2022)
Background/Aim. Renal transplantation is the best and preferred way of treating patients with end-stage renal disease, as it offers improved survival and better quality of life compared to dialysis. The aim of this study was to present single-center (Military Medical Academy in Belgrade, Serbia) results of the kidney allograft and patient survival from 1996 to 2017. Methods. A retrospective 22-year cohort study was conducted. Variables of interest were graft and patient survival in kidney transplanted patients. Age, gender, serum creatinine levels, and induction therapy after transplantation were analyzed in this group of patients as well. Results. Among 386 transplanted patients, 316 had a living donor and 70 patients had a deceased donor. Pre-emptive renal transplantation was done in 29 (7.5%) patients and AB0-incompatible kidney transplantation in 21 (5.4%) patients. One-year, 5-year, 10-year, and 20-year overall patient survival after kidney transplantation in the observed group was 97.7%, 95.3%, 93.8%, and 91.7%, respectively. One-year, 5-year, 10-year, and 20-year graft survival in our patients were 93.8%, 85.5%, 78.5%, and 73.3%, respectively. Conclusion. The outcome of graft and patient survival in the Belgrade Military Medical Academy kidney transplantation program is good and in line with the leading world medical centers.
Keywords: age factors; creatinine; allografts; graft, survival; kidney transplantation; sex factor.